Controllable construction of oxygen vacancies by anaerobic catalytic combustion of dichloromethane over metal oxides for enhanced solar-to-hydrogen conversion. Issue 10 (12th August 2019) - Zhang, Sufen; Liu, Jianni; Dong, Xiaoyang; Jia, Xiaoxia; Gao, Ziwei; Gu, Quan
Abstract : A facile anaerobic catalytic combustion method is used for controllable oxygen vacancy construction of metal oxides for enhanced solar-to-hydrogen conversion. Abstract : Defect engineering is an effective strategy to modify metal oxide semiconductor photocatalysts, but the general strategy for controllable construction of defects remains a great challenge. Herein, we report a facile anaerobic catalytic combustion method using a volatile organic compound (CH2 Cl2 ) as a reactant for controllable construction of oxygen vacancies (VO ) in TiO2 for enhanced solar-to-hydrogen conversion. This strategy has the general applicability for the preparation of VO enriched metal oxides including TiO2 (001), rutile TiO2, MoO3, ZnO, and WO3 . The results of photocatalytic tests show VO -dependent photocatalytic H2 production activities under both visible light and solar light irradiation. The surface VO on TiO2 enable the visible light harvesting of TiO2 and provide adsorption sites for H2 evolution, and most importantly, they as charge carrier traps facilitate the separation of the photogenerated charges by intrinsic excitation with UV light irradiation, leading to greatly enhanced overall solar light activity of TiO2 . However, bulk VO as the recombination centers hamper the photogenerated charge separation process, causing significantly decreased visible light and solar light photocatalytic activities. Moreover, we find that the synergistic effects of Pt cocatalysts and VO further enhance the solar-to-hydrogen conversion over TiO2 . This work provides a general guide for constructing VO on various metal oxide semiconductors and offers scope for the future development of VO enriched metal oxide photocatalysts for efficient solar energy conversion.